Contrasting effects of repetition across tasks: implications for understanding the nature of refractory behavior and models of semantic memory. - Forde, E; Humphreys, G (2007)
We describe a patient (J.M.) who showed "refractory" behavior in picture-word matching tasks--that is, his performance became poorer when items were repeated. This contrasts with the facilitatory effects of repetition usually observed in normal participants. We show for the first time that there can be facilitatory effects of repetition on some tasks, even though refractory behavior is shown on the same items in other tasks. In particular, in Experiments 1 and 2, we demonstrate that J.M. showed contrasting effects of repetition across different components of the language system: There were facilitatory effects of repetition priming on lexical decision but refractory behavior on picture-word matching. In Experiments 3 and 4, we demonstrate that J.M. showed contrasting effects of repetition within the same system (semantic memory). His performance became refractory when items were repeated in picture-word matching (Experiment 3), but it was facilitated when items were repeated in superordinate categorization (Experiment 4). These contrasting patterns of facilitation and interference from repetition priming have implications for understanding the nature of refractory behavior and for constraining theoretical accounts of semantic memory.